Utility of paediatric logistic organ dysfunction score in predicting mortality in children admitted to PICU at a tertiary care centre - Gobbur, Soujanya; Badakali, Ashok; Pol, Ramesh; Neelannavar, Ramesh (International Journal of Contemporary Pediatrics, 2023)
Background: Critically ill children are typically characterized by multiple organ dysfunctions. The use of Paediatric logistic organ dysfunction-2 (PELOD-2) scoring systems has recently been replicated in the paediatric population for morbidity and mortality predictions. Objective of the study was to study the PELOD 2 score in predicting mortality in paediatric intensive care unit within 1 hour of admission. Methods: This was prospective observational study conducted at S Nijalingappa Medical College and Hanagal Shri Kumareshwar Hospital, Bagalkot for period of 16 months. Children aged from 1 month to 14 years admitted to PICU were included in the study and patients whose parents refuse to give consent, age less than 1 month or more than 14 years, those discharged against medical advice were excluded from the study. Venous blood sample were collected within one hour of admission and were analyzed for serum creatinine, serum lactate, total leukocyte count and platelet count and arterial blood sample were collected and paO2 and paCO2 were analysed. Results: Total sample size of study was 80, out of which 52 patients had PELOD 2 score of (<4), 14 patients had score of (5-9), 11 patients had score of (10-14) and 3 patients had score >15.Among total 80 patients 66 survived and 14 died (17.5%). Of the 14 deaths, 3 patients had PELOD 2 score of >15 and 9 had score of 10-14. Pelod-2 score >9 had requirement of mechanical ventilation in 68.4%. Conclusions: Higher the PELOD-2 score on day 1of admission has higher the mortality.